A novel consumer-centric metric for evaluating hearing device audio performance - Manchaiah, Vinaya; Taddei, Steve; Bailey, Abram; Swanepoel, De Wet; Rodrigo, Hansapani; Sabin, Andrew (Frontiers in Audiology and Otology, 2024)
Background and Aim The emergence of direct-to-consumer hearing devices has introduced confusion in making appropriate choices, highlighting the need for users to be well-informed for optimal device selection. Currently, no established metric offers insights into the sound performance of these devices. This study aimed to introduce and assess a novel consumer-centric metric (i.e., SoundScore) for hearing device audio performance. Method The SoundScore metric was created based on five dimensions of hearing device audio performance (i.e., speech benefit in quiet and moderate, speech benefit in loud, own voice perception, feedback control, streamed music sound quality). Tests were conducted under lab conditions with an acoustic manikin using two fitting protocols meant to approximate (1) real-world default device settings for a mild-to-moderate sloping hearing loss (“Initial Fit”) and (2) an audiological best-practices approach (“Tuned Fit”). A total of 41 hearing devices comprising 10 prescription hearing aids (Rx-HA), 10 self-fitting over-the-counter hearing aids (OTC-SF), 8 pre-set based over-the-counter hearing aids (OTC-PS), and 13 personal sound amplification systems (PSAPs) were evaluated. Results SoundScore varied significantly between device classifications with Rx-HA yielding the highest average scores and PSAPs the lowest. SoundScore also varied with fitting method, whereby preset based devices scored lower on average than devices programmable by fitting software. Performance across the five composite sound performance metrics generally improved between “Initial” and “Tuned” fits for Rx-HA. However, this was not observed with OTC-SF. Also, no significant difference in SoundScore was found between devices of different form factors (i.e., BTE vs. ITE). Conclusions Initial findings suggest that the SoundScore can effectively distinguish between the audio performance of different hearing aids, offering consumers a valuable decision-making tool. Future studies should examine the relationship between the SoundScore and consumer hearing aid benefit/satisfaction.